Public Education as a Strategy for Human Resource Development in Preventing Cybercrime in Indonesia - Ega Satya Nugraha; Chairul Muriman Setyabudi; Muhammad Ezra Aminanto (Transpublika Publisher, 2025)
Cybercrime has escalated significantly in Indonesia over the past five years, with offenses such as online gambling, fraud, and data manipulation increasing in both frequency and sophistication. This study investigates the role of public education, particularly the National Digital Literacy Movement (GNLD), in addressing these challenges by applying a descriptive qualitative design that relies on literature review as the primary method. Data were drawn from secondary sources, including Bareskrim cybercrime reports from 2020 to 2024 and digital literacy assessments issued by the Ministry of Communication and Informatics. The analysis focuses on suburban and semi-rural regions where digital vulnerability remains high despite broader program outreach. Findings indicate a structural disconnect between the expanding scale of digital literacy initiatives and the persistent weakness of the “Digital Safety” pillar, which consistently scores lowest on the national index. This gap suggests that general awareness alone does not ensure behavioral change or online protection. The study concludes that cybercrime prevention efforts must move beyond surface-level education and adopt targeted, behaviorally informed strategies that align with actual regional threat patterns. Strengthening this approach is essential to building meaningful digital resilience, especially in communities facing the greatest risks.